Analisis Portofolio Optimal Dengan Metode Markowitz Dan Metode Sharpe Pada Perusahaan Infrastruktur, Utilitas, Dan Transportasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019 - Elita Yuvika Wulandari; Aprilina Susandini (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
Many investors are interested in financial investment as a means of developing their own funds. Investors make investments with the aim of obtaining maximum dividends with minimal risk, namely by compiling a portfolio. Determining the optimal portfolio can be done using the Markowitz method and the Sharpe method. This study is to determine which stocks are included in the optimal portfolio using the Markowitz method and the Sharpe method on the shares of Infrastructure, Utilities and Transportation Companies in 2019. Based on the results of research conducted at Infrastructure, Utilities and Transportation companies in 2019. The optimal portfolio proportion using the Markowitz method was obtained by 7 companies, namely PGAS (proportion 82.32%), POWR (proportion 12.11%), TLKM (proportion 72.74%), TCPI (proportion 43.48%), TPMA (proportion 90.46%), GHON proportion (75.03%), and JSMR (proportion 57.50%). Meanwhile stocks classified as optimal portfolio based on the Sharpe method include PGAS (proportion of 57.91%), TLKM (proportion of 10.41%), TCPI (proportion of 13.09%), TPMA (proportion of 62.50%), SOCI (proportion of 4.45%), GHON (proportion 8.63%), and JSMR (proportion 18.64%). The calculation results show that out of the total of 21 companies, it is recommended to invest in 6 companies that have equally positive values based on the two methods such as PGAS, TLKM, TCPI, TPMA, GHON, and JSMR. By compiling a portfolio can optimize the level of profit to be achieved and minimize the level of investment risk.